Kewajiban dan Hak Warga Negara dalam Demokrasi yang Bersumber pada Kedaulatan Rakyat dan Musyawarah untuk Mufakat - Tasya Alifia Izzani; Rahmadini Rahmadini (Garuda: Jurnal Pendidikan Kewarganegaraan Dan Filsafat, 2024)
This study reviews the obligations and rights of citizens in the context of democracy which is based on popular sovereignty and the principle of deliberation to reach consensus. Democracy based on popular sovereignty places citizens as the highest authority in the state. Citizenship obligations include active participation in the political process, respect for the law, and positive contributions to the development of society. Meanwhile, citizens' rights include the right to freedom of opinion, the right to vote and be elected in general elections, as well as the right to receive fair and proportional legal protection. The importance of deliberation to reach consensus is also emphasized as a method for resolving differences of opinion in democratic life. This study highlights the active role of citizens in maintaining and developing an inclusive and just democracy.